Near-death experiences, and others - Gottlieb, Robert, 1931- (Farrar, Straus and Giroux, 2018)
This new collection from the legendary editor Robert Gottlieb features twenty or so pieces he's written mostly for The New York Review of Books, ranging from reconsiderations of American writers such as Dorothy Parker, Thornton Wilder, Thomas Wolfe ("genius"), and James Jones, to Leonard Bernstein, Lorenz Hart, Lady Diana Cooper ("the most beautiful girl in the world"), the actor-assassin John Wilkes Booth, the scandalous movie star Mary Astor, and not-yet president Donald Trump. The writings compiled here are as varied as they are provocative: an extended probe into the world of post-death experiences; a sharp look at the biopics of transcendent figures such as Shakespeare, Molière, and Austen; a soap opera-ish movie account of an alleged affair between Chanel and Stravinsky; and a copious sampling of the dance reviews he's been writing for The New York Observer for close to twenty years.